Stability Investigation of Difference Schemes for Gas Dynamics Equations*. Issue 12 (2016) - Akhmetzianov, A.; Boronin, I.; Salnikov, A.; Shevlyakov, A.
Abstract: Problems of effective control of gas flow are closely related to the system of equations describing the motion of the gas in the gas collection network of a gas field. Due to the great length of gas gathering networks and the necessity to consider the compressibility of the gas, pressure and flow distributions are described by the Navier-Stokes equations. For the successful application of difference methods for solving these equations, their stability must be thoroughly investigated. This is the goal of current article.